ANALISIS PEMIKIRAN SISWA TENTANG PROSES PEMBELAJARAN MENGGUNAKAN KURIKULUM CAMBRIDGE ASSESSMENT INTERNATIONAL EDUCATION DALAM KELAS INTERNASIONAL X SMA NEGERI 3 PONOROGO - Fajrina, Rizky Aprilia; Yanti, Khairunisa Dwi; Damayanti, Putri; Asiyah, Siti; Rohmatin, Yunia Dwi (Universitas Muhammadiyah Ponorogo, 2023)
The world of education is very important for everyone and the younger generation. Education aims to educate and increase one's potential. Education aims to develop student character values. which includes components of knowledge, awareness, and skills of students based on English. This research is motivated by the researcher's interest in international classes while doing internships at certain schools that are carried out by every FKIP student. The international class at SMAN 3 Ponorogo is the first high school/K/equivalent level international class in Ponorogo, therefore the researcher wants to find out more in-depth information about the international class at SMAN 3 Ponorogo. This study aims to determine the implementation of learning evaluation and analysis of students' thoughts in international classes with Cambridge Assessment International Education curriculum-based learning. The international class itself is a way to develop students' potential to improve English skills and to think critically, logically and systematically analyze students at SMAN 3 Ponorogo, East Java. This study uses a qualitative method by describing or describing activities in the international class. Data was collected using observation techniques, interviews, and documentation. The research subjects used in this study were a teacher and three international class students, where previously the researcher had observed the X international class at SMAN 3 Ponorogo. In this study, researchers can conclude that the existence of this international class, although it faces many challenges, has a good impact on students and teachers who have the responsibility to teach in this class. The impact that looks striking is the use of English used in the teaching and learning process so that teachers and students in international classes are required to understand and understand English properly and correctly